State of Georgia Judgment in Supreme [Court], Camden County, May 1869 - State of Georgia (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1869)
State of Georgia Judgment in Supreme [Court], Camden County, 1869. Hand written document on ruled paper. Elizabeth A. Riley vs. Nathaniel B. Stafford for settlement of debt of $474.50. Camden County, Georgia. May 15, 1869. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Judgments; Court Records; Records and correspondence